Simultaneous detection of salmonella sp. In consumption chicken eggs using mpn-pcr technique / Farhani Ahmad - Ahmad, Farhani (Faculty of Applied Sciences, 2016)
Foodborne illness called salmonellosis universally found on fresh product. This study were to determine the prevalence Salmonella sp.in farm chicken eggs and free-range chicken eggs in Kuala Pilah, Negeri Sembilan. This study was performed using the Most Probable Number (MPN) and Polymerase Chain Reaction (PCR) method. The prevalence of Salmonella sp. in a total of 10 farm chicken eggs and free-range chicken eggs were 20% (1/5) and 60% (3/5) respectively, with estimated values varying from 150 to 1100 MPN/g. The causative factors will be the different ways of chicken's living style and how the eggs were cooked. In addition, abandoning temperature and expiration date will also contribute to the growth of Salmonella sp. This study will attract all consumers to become more alert on the biosafety level of their daily diet especially chicken eggs.